ANALISIS PERBANDINGAN PERFORMA SERVER DISKLESS REMOTE BOOT IN LINUX (DRBL) DAN LINUX TERMINAL SERVER PROJECT(LTSP) (STUDI KASUS: LABORATORIUM TEKNIK INFORMATIKA UNIVERSITAS TANJUNGPURA) - Wijdani, Muhammad Mundzir (JUSTIN (Jurnal Sistem dan Teknologi Informasi), 2014)
There are two ways to build a diskless network based on Linux operating system, Diskless Remote Boot in Linux (DRBL) and Linux Terminal Server Project (LTSP). This research was done to both method by implement it to the computer network in Informatical Engineering’s laboratory of Tanjungpura University. This research aimed to build a diskless network by using both method, DRBL and LTSP, then compare the server performance, in this case is the comparison of processor and memory performance to find which method is best to use in Informatical Engineering’s laboratory of Tanjungpura University. This research using litterature study method and deep analysis about anything related to DRBL and LTSP so that it can be implement in the computer network in Informatical Engineering’s laboratory of Tanjungpura University. Those include schematic plan of the diskless network that will be use, how the DRBL and LTSP work and analysis to whom will be the user of the diskless network. Based on the research data, it can be seen that the processor’s work loadin the DRBL server in not affected by the use of application in client eventhough the number of the client connected to the DRBL was increasing. The opposite thing happened to the work load of DRBL server memory. There was an increasing of the memory work load as the use of many applications/software by the client in the DRBL network. In the LTSP, the processor’s work load was affected by the use of application in LTSP client. As the processor’s work load increased, the memory work load was also affected by the number of client and varian of application used by client. Problem founded in the DRBL was the client computer and the low VGA resource in the DRBL which can’t display the operating system desktop interface Ubuntu. Meanwhile in the LTSP, there was no problem with the client computer and the low VGA resource. Conslusion, the most suitable diskless network to be use in the Informatical Engineering’s laboratory of Tanjungpura University is LTSP method, compared to the DRBL, because the LTSP can optimize the client computer with low VGA resource which mostly used in Informatical Engineering’s laboratory of Tanjungpura University.